Kinerja Pelayanan Moda Transportasi Online Roda Dua Wilayah Layanan Kabupaten Pinrang (Kurir Online) - Sri Yuliana Wali; Jasman; Misbahuddin (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study aims to examine the operasional performance of online motorcycle courier services and the factors considered by consumenrs when choosing online motorcycle courier services. Customers who have utilized online courier services are the subject of this research employing the Importance Performance Analysis (IPA) approach to determine that there are 90 respondents. The results show that 90 customers are mostly female (60%), have a high school education (62%), work as students (37%), are aged 21-30 years (54.4%), own a motorcycle as their private vehicle (82%), have an income of ≤ Rp. 1,000,000 (43%), make choices based on products (54%), use services once a week (36%), and order online courier services during the day (11:00 AM – 2:00 PM WITA). For the Importance Performance Analysis (IPA) method, the average expectation level is 4.65 and the average performance level is 4.03. From the IPA quadrant diagram, one indicator that needs improvement falls into Quadrant I. Five indicators that need to be maintained are in Quadrant II, five indicators with still low priority are in Quadrant III, and one indicator considered excessive falls into Quadrant IV. Consumer considerations in selecting online courier services are based on reasons where the majority of respondents state that safe and comfortable service accounts for 52%, and the advantages of using online courier services due to easy ordering account for 46%.